Feral Rye (Secale cereale) Control in Winter Canola in the Pacific Northwest. (March 2016) - Young, Frank L.; Whaley, Dale K.; Lawrence, Nevin C.; Burke, Ian C.
Abstract : In the Pacific Northwest (PNW), feral rye is a predominant winter annual grass weed in the low-rainfall region where a winter wheat–summer fallow rotation has been practiced for more than 130 yr. Recently, producers began including winter canola in their rotation, which provides additional herbicide options to control feral rye. A 3-yr study was conducted in Washington to determine the efficacy of clethodim, quizalofop, and glyphosate on feral rye control and winter canola yield. During the first year of the study herbicides were applied in the spring, and they increased canola yield and decreased feral rye biomass, density, and seed production similarly when compared with the nontreated control. During the last 2 yr of the study, split applications of quizalofop and glyphosate were the most effective treatments for controlling rye (> 95%) and increasing canola yield. In general, clethodim was less effective than both quizalofop and glyphosate in controlling feral rye. Results from this study indicate that quizalofop in conventional or glyphosate-resistant winter canola and glyphosate in glyphosate-resistant winter canola can effectively control feral rye.